(untitled) (CIPEEX, 2025)
This research aims to demonstrate the impact caused by the pandemic resulting from COVID-19 on the professional lives of working mothers, considering that the public calamity triggered a health and, at the same time, economic crisis throughout the world. Through the study of scientific articles and other academic productions, combined with bibliographic review and analysis of official data, it was possible to understand the Brazilian scenario, so the study was necessary to answer how the pandemic affected the professional lives of mothers who work outside the home and how the law addressed this issue and, also, the difficulties that mothers faced in remaining in the job market, reconciling their activities with the dynamics of the home and raising their sons and daughters. The theoretical and data study allowed us to understand maternal evasion from the formal job market and their migration to informality. It is concluded that the pandemic caused several financial difficulties, loss of formal jobs and, also, the absence of effective public policies for working mothers. The social and academic relevance of the research is justified due to maternal vulnerability in the job market as, in the midst of a crisis, mothers are part of the first groups to suffer negative impacts due to the evasion of jobs and legal protection.